The respiratory responses of an amphibious snail Pomacea lineata (spix, 1827), to temperature and oxygen tension variations - Santos, Cristina A.Z; Penteado, Carlos H.S [UNESP]; Mendes, Erasmo G (Elsevier, 1987)
1. 1. The respiratory responses of Pomacea lineata to short-term (or acute) exposure to temperature and oxygen tension variations were investigated in animals acclimated to 25°C. 2. 2. The respiratory rates increased with rising temperatures; this increase was sharper between 15 and 25°C than at any other temperature interval; a tendency to a plateau in the RT curve was recorded between 25 and 35°C. 3. 3. All animals survived well to 1 hr exposure to the extreme temperatures used (5 and 40°C). 4. 4. In two different experimental approaches, the animals showed ability to regulate the respiratory rate in declining oxygen tensions, at least down to 10% (70.8 mmHg) oxygen. 5. 5. After 1 hr exposure to hypoxic conditions, P. lineata exhibited the pattern of underpayment of the oxygen debt acquired. 6. 6. Six out of ten animals survived after 40 days in anoxia (100% nitrogen). © 1987.